DIABETES MELLITUS TREATMENT USING HERBAL DRUGS - Sharapova Nozima Erkinjonovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation: The use of medicinal herbs is widespread among patients with diabetes mellitus. The purpose of this study is to determine the prevalence of herbal use among diabetic patients and to identify which herbs are most commonly used. In addition, the study examines the impact of certain demographic characteristics on the use of herbal remedies.